A pilot cluster randomized controlled trial assessing uptake of PrEP and contraception in hair salons in South Africa - Ingrid V. Bassett; Joyce Yan; Sabina Govere; Sthabile Shezi; Lungile M. Ngcobo; Shruti Sagar; Jana Jarolimova; Dani Zionts; Anele Khumalo; Zinhle Zwane; Christina Psaros; Nduduzo Dube; et al. (BMC Public Health)
Abstract Background Women in South Africa have a high burden of HIV infections, STIs, and unintended pregnancies. Women congregate regularly in hair salons, which may be useful venues for HIV and sexual and reproductive health (SRH) services. Our objective was to assess the uptake of PrEP and contraception in hair salons in South Africa. Methods We conducted a pilot cluster randomized controlled trial to evaluate uptake of a hair stylist-initiated, nurse-supported intervention offering a dynamic choice of contraception (oral or injectable), STI testing and treatment, and oral PrEP in 3 salons in urban KwaZulu-Natal. Rapid HIV testing was performed in a private area at enrollment and each PrEP dispensing. Women could receive contraception and/or oral PrEP at the initial visit or opt in at a later visit. We defined uptake as the proportion of eligible women who accepted salon-based PrEP and/or salon-based contraception at any visit. Control salon participants completed surveys and were referred to clinic. We assessed predictors of PrEP uptake among intervention participants using univariate logistic regression and multivariable logistic regression with age and potential predictors from the univariate analyses. Results Among 134 participants in intervention salons, the median age was 26 years (IQR 22–29). 75% reported visiting the salon at least every 2 months. 27% were using hormonal contraception at enrollment, 31% reported a self-perceived moderate or great chance of getting HIV in the next year, 33% thought their primary sex partner had other partners, 65% did not use condoms in the past month, and 11% reported intimate partner violence (IPV). About half (49%) accepted salon-based PrEP, and 89% accepted salon-based contraception during the study. Adjusting for age, uptake of salon-based PrEP was associated with experiencing IPV (aOR 4.20, 95%CI: 1.02, 17.36). Conclusions When offering a dynamic choice of integrated SRH services in urban hair salons in South Africa, we reached young women with risk factors for HIV, STIs, and unintended pregnancies. Hair salons are a novel venue for reaching young women who may not perceive themselves at risk for HIV, STIs, and unintended pregnancies. Trial Registration Clinicaltrials.gov identifier: NCT04222504. Registered 01-08-2020.